Identyfikacja regionalna mieszkańców pogranicza polsko-niemieckiego - Gołdyka, Leszek (Człowiek i Społeczeństwo, 2017)
According to the author about a half of the Polish-German borderland inhabitants are “the winners” of the systemic transformation, they are pragmatic individualists and materialists. In their case identification with any other person than themselves and members of the closest family is rare. The other half are members of enclaves and “tribes”. Solidarity, which may be found in their system of values, is however limited to their “fellows of the same mind”, thus it has a particular character. These are the “losers” of the transformation. The feeling of material deprivation, their identification particularism generates and enhances a reluctant attitude to the reconstruction of the German cultural heritage in the Polish western borderland. According to the author, the reconstruction of this heritage creates the feeling of non-obviousness as to the possession of the western borderland, thus evoking a negative attitude to everything that is German or, generally, ethnically “strange”. The first ones treat land in a materialist, instrumental manner (as “plots of land” for development), they may recognize it as a subject of a profitable transaction, not making it the subject of a moral dilemma whether the achievement of their interest reduces the economic strength of the Polish state. For the other ones, land has got a symbolic value. In the Author’s opinion, the inhabitants of the western borderland, though in many objective aspects similar, are not subjectively close to one another. Dichotomously divided, they create a territorial group, not a community. On account of the individualistic, pragmatic and materialistic orientation of one half of the inhabitants, in this paper the Polish – German borderland is called a space of identification vacuum, whereas on account of the enclave-like and tribal orientation of the other half of its inhabitants it is called a space of identification failure.